Pengaruh Latar Belakang Pendidikan dan Kualitas Pelatihan Kepala Desa Terhadap Pemahaman Laporan Keuangan Desa - Angelina, Agnes Maya; Adi, Priyo Hari (E-Jurnal Akuntansi; Vol 32 No 6 (2022), 2022)
This study aims to determine the effect of educational background and quality of village head training on understanding village financial reports in Semarang Regency. The sampling technique used is 100 simple random sampling. This research is a quantitative research with multiple linear regression analysis method. The results of the study show that educational background and training quality variables have a positive effect on understanding financial statements as evidenced by all beta coefficients being positive. Keywords: Educational Background; Quality of Training; Understanding of Financial Statements